Peningkatan Keselamatan Lalu Lintas Pada Ruas Jalan Hayam Wuruk Di Kabupaten Jember - Syaban, Alfath Satria Negara; Azizah, Elvira; Wijianto, Wijianto (Jurnal Keselamatan Transportasi Jalan (Indonesian Journal of Road Safety), 2021)
The number of accidents that occurred in Jember Regency during the last 5 (five) years has decreased, although in some years there has been an increase and caused the number of fatalities (death, serious injuries, minor injuries) to increase every year. From the data obtained, it can be seen that one of the roads that often has accidents is the Hayam Wuruk road. Traffic flow and speed conditions on the Hayam Wuruk road are quite high due to its function as arterial roads and national roads, but the land use around these roads which includes shops, shopping centers, offices, and schools causes frequent conflicts and traffic problems. especially in the field of road safety, both driver safety and pedestrian safety. This study aims to increase the level of safety in traffic for both drivers and pedestrians on the Hayam Wuruk road, Jember Regency. This is carried out by observing and identifying the existing conditions along the Hayam Wuruk road including road performance conditions, traffic safety conditions and behavioral conditions for road users on these roads, so that handling proposals are obtained based on the results of data analysis that has been collected both primary and secondary data. secondary data. The results showed that the high number of accidents on the Hayam Wuruk road in Jember district was mostly caused by errors from human factors. Therefore, there is a need for a social approach in the form of increasing awareness and safety for drivers in the form of applying canalization on the leftmost lane to limit two-wheeled vehicles that interfere with traffic flow on the main road lane, making noise tape and installing speed limit signs to protect the safety and comfort of users.